Study Design Algorithm. - Andrews, Jeff; Likis, Frances E. (Journal of Lower Genital Tract Disease, 2015)
Objectives: To aid authors in correctly naming their study design, to assist readers and reviewers who must decide what the design was for some published studies, and to provide consistency in evaluating the design of published studies, especially for those conducting systematic reviews and evidence synthesis.Methods: An annotated algorithm method is used to prompt serial questions and analysis to identify a single study design.Results: The algorithm begins with a research article. Primary clinical research is divided into experimental and observational studies. Key determinants include identifying the study question and the population, intervention, comparison, and outcome. Experimental therapy and prognosis studies are subdivided into 4 design types. Observational therapy and prognosis studies are subdivided into 7 design types. Experimental diagnosis and screening studies are subdivided into 2 types. Observational diagnosis and screening studies are subdivided into 5 types.Conclusions: An annotated algorithm may be used by authors, readers, and reviewers to consistently determine the design of clinical research studies.